Low temperature synthesis of hexagonal Bi2Te3 nanoplates using an open reactor and its effect on their physicochemical properties - Reyes Verdugo, Laura A.; Martínez Carreón, María de Jesús; Gutiérrez Lazos, C. D.; Solis Pomar, Francisco J.; Quiñones Galvan, Jose G.; Pérez Tijerina, Eduardo Gerardo (John Wiley & Sons, 2024)
Tis report presents the physicochemical properties of hexagonal Bi2Te3 nanoplates chemically prepared in an open reactor at a lower temperature (140°C) than those reported for controlled condition techniques. Te samples were drop-cast on glass and FTO substrates for subsequent structural, chemical, and thermoelectric analyses. Te electron microscopy analysis demonstrated that samples precipitated in highly crystalline hexagonal nanoplates, grown along the [0 1 5] plane of the rhombohedral phase of Bi2Te3. Te nanoplates exhibited an extension of up to several hundred nanometers, with thicknesses in the range of 20–40 nm, and with an interplanar spacing of 0.321 nm. A vibrational mode at 120 cm−1 due to the breaking of the symmetry of the Bi2Te3 crystal along the C axis was observed by Raman spectroscopy. XPS results showed that despite the strong reactivity of Te2− ions with ambient oxygen, the crystallization of Bi2Te3 hexagonal nanoplates is feasible without controlled vapor pressure and at a lower temperature than reported in other works. Finally, the measurement of the Seebeck coefficient exhibited a p-type conductivity of Bi2Te3, with a maximum value of 169 μV/K within the temperature range of 300 to 320 K.